Exploring the relationship between the COVID-19 pandemic and changes in travel behaviour: A qualitative study. (September 2021) - Yang, Yilin; Cao, Mengqiu; Cheng, Long; Zhai, Keyu; Zhao, Xu; De Vos, Jonas
Highlights: COVID-19 has greatly changed travel demand, trip purposes and mode choices. Socially disadvantaged groups are more likely to experience transport-related exclusion. Policymakers and urban planners should pay greater attention to social inequities. Public transport systems should be further developed through network expansion. Abstract: During the COVID-19 crisis, a series of measures were taken to restrict travel and social activities outside the home in order to curb the pandemic and ameliorate its negative effects. These unprecedented measures have had a profound impact on the number and purposes of trips and modes of travel. In China, although the pandemic is now generally under control and transport availability has returned to nearly normal, the extent of the changes in travel behaviour wrought during and after the pandemic still remains unclear. Therefore, the aim of this paper is to investigate the differences in individual travel behaviours during and after the COVID-19 pandemic, using Huzhou as an example. Semi-structured interviews were used to examine the influence of COVID-19 on the travel behaviour and perceptions of different groups. The results indicate that, initially, travel demand was greatly reduced. Second, decreased travel reduced participation in activities, which can have adverse effects on people's health as well as their subjective well-being. Third, the degree and duration of such impacts varied from person to person. Students, lower income cohorts, groups living in small communities with insufficient green spaces, and those working in tourism, catering, informal businesses and transport-related sectors were more vulnerable than others. Policymakers, urban and transport planners should therefore pay attention to the social inequities that arise from unequal access to transport and heterogeneity between individuals. Additionally, public transport systems require further development to promote social cohesion.